Games for actors and non-actors - Boal, Augusto (Routledge, 2022)
"Games for Actors and Non-Actors is the classic and bestselling book by the founder of Theatre of the Oppressed, Augusto Boal. It sets out the principles and practice of Boal's revolutionary method, showing how theatre can be used to transform and liberate everyone - actors and non-actors alike! This new third English edition includes recently uncovered interviews and essays from the 1970s, some of which featured in the earliest Portuguese edition of this book and a new essay by the theatre director Sergio de Carvalho, which looks at Boal's work in the context of Brazilian theatre and politics over the past fifty years. This is a vital handbook for theatre makers and activists of all kinds who want to deepen their understanding of the theory and practice of Boal's Theatre of the Oppressed. It is also an excellent introduction for those new to the system"-- Provided by publisher.